2022
DOI: 10.1038/s42255-021-00518-0
|View full text |Cite
|
Sign up to set email alerts
|

PSD3 downregulation confers protection against fatty liver disease

Abstract: Fatty liver disease (FLD) is a growing health issue with burdening unmet clinical needs. FLD has a genetic component but, despite the common variants already identified, there is still a missing heritability component. Using a candidate gene approach, we identify a locus (rs71519934) at the Pleckstrin and Sec7 domain-containing 3 (PSD3) gene resulting in a leucine to threonine substitution at position 186 of the protein (L186T) that reduces susceptibility to the entire spectrum of FLD in individuals at risk. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…Briefly, for the generation a liver organoid model composed of primary human hepatocytes (PHH), cryopreserved primary human hepatocytes (donor BGW-M00995-P, BioIVT, Belgium, male, 50 years of age, BMI 20.4) were used [15,16]. Cells were seeded on ultra-low attachment 96-well plates (Corning) at 2000 viable cells per well onto 100 µL of serum containing complete medium.…”
Section: And 3d Cell Culturementioning
confidence: 99%
“…Briefly, for the generation a liver organoid model composed of primary human hepatocytes (PHH), cryopreserved primary human hepatocytes (donor BGW-M00995-P, BioIVT, Belgium, male, 50 years of age, BMI 20.4) were used [15,16]. Cells were seeded on ultra-low attachment 96-well plates (Corning) at 2000 viable cells per well onto 100 µL of serum containing complete medium.…”
Section: And 3d Cell Culturementioning
confidence: 99%
“…and their downregulation results in reduced hepatic lipids in vitro and protects against fatty liver in vivo in mice [29].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of SEL1L2 and SYT9, gene loci showing evidence of monogenic control of lipids in our study have been associated with disease-relevant phenotypes (e.g., body mass index), biochemical variables (e.g., creatinine) and behavioral traits in the GWAS repository ( , accessed on 1 May 2022). Interestingly, multiple SNPs, the locus of the gene encoding pleckstrin and the Sec7 domain containing 3 (PSD3), which controls the level of a carnitine in our study, have been consistently associated with triglycerides and cholesterol levels as well as type 2 diabetes and obesity [ 28 ], and their downregulation results in reduced hepatic lipids in vitro and protects against fatty liver in vivo in mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pnpla3-ASO can decrease the level of 1-acylglycerol-3-phosphate O-acyltransferase (AGPAT) to affect the esterification of fatty acids, thereby reducing the synthesis of phosphatidic acid (PA) (Kumashiro et al, 2013). A mutation of leucine 186 to threonine in Pleckstrin and sec7 domain-containing 3 (PSD3) has been reported reducing the risk of fatty liver (Mancina et al, 2022). As predicted, Psd3-ASO downregulates the expression of PSD3 in mice induced by a NASH diet, and decreases the expression of the lipogenic enzymes acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), and stearoyl-CoA desaturase 1 (SCD1), which consequently alleviates hepatic steatosis (Mancina et al, 2022).…”
Section: Application Of Antisense Oligonucleotide In Non-alcoholic Fa...mentioning
confidence: 99%
“…A mutation of leucine 186 to threonine in Pleckstrin and sec7 domain-containing 3 (PSD3) has been reported reducing the risk of fatty liver (Mancina et al, 2022). As predicted, Psd3-ASO downregulates the expression of PSD3 in mice induced by a NASH diet, and decreases the expression of the lipogenic enzymes acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), and stearoyl-CoA desaturase 1 (SCD1), which consequently alleviates hepatic steatosis (Mancina et al, 2022). Whole genome-wide and exome studies have found that genetic variants near the γ-secretase subunit nicastrin (Ncst) are associated with HDL cholesterol (HDL-c) and LDL cholesterol (LDL-c) levels.…”
Section: Application Of Antisense Oligonucleotide In Non-alcoholic Fa...mentioning
confidence: 99%